Expert opinion on the management and follow-up of uveitis patients during SARS-CoV-2 outbreak. (2nd July 2020) - Stanescu-Segall, Dinu; Sales de Gauzy, Thomas; Reynolds, Rhianon; Faes, Livia; Pohlmann, Dominika; Pakzad-Vaezi, Kaivon; Ting, Daniel; Saadoun, David; Ambati, Jayakrishna; Loewenstein, Anat; Bodaghi, Bahram; de Smet, Marc D.; et al.
ABSTRACT: Introduction: Routine medical and ophthalmic care is being drastically curtailed in the context of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. Uveitis patients require particular attention because of their theoretical risk of viral infection, in the context of therapeutic immunosuppression. Areas covered: This collaborative work proposes practical management and follow-up criteria for uveitis patients in the context of the ongoing SARS-CoV-2 pandemic. Expert opinion: Management should proceed as usual when access to health care possible in patients who do not belong to a group at high risk of severe SARS-CoV-2 infection, and in uncontrolled uveitis cases. In case of reduced access to eye clinics or high risk of SARS-CoV-2 infection, patients' management should be stratified based on their clinical presentation. In non-severe uveitis cases, the use of systemic steroids should be avoided, and local steroids preferred whenever possible. In uncontrolled situations where there is real risk of permanent visual loss, high-dose intravenous steroids and/or systemic immunosuppressants and/or biotherapies can be administered depending on the severity of eye disease. Immunosuppressive therapy should not be withheld, unless the patient develops SARS-CoV2 infection.